Simulation-based training in emotional intelligence and self-esteem: enhancing effectiveness and wellbeing in healthcare - Pérez-Fuentes, María del Carmen; Molero Jurado, María del Mar; Romanos-Rodríguez, Armando; Barragán Martín, Ana B.; Gómez-Gómez, Francisco J.; Aguado-Campos, Javier (Frontiers in Public Health, 2025)
IntroductionThe study focuses on the training of health professionals, traditionally based on technical skills and specialized knowledge. However, the importance of integrating emotional intelligence and self-esteem has gained recognition for its impact on the quality of patient care and professional wellbeing. This study examines how targeted interventions in these areas can improve wellbeing and professional effectiveness in primary care settings.MethodA multicenter study was conducted with a pre-experimental design, assessing participants before and after the intervention, with no control group. Participants were 106 physicians and nurses in primary care centers in Andalusia, Spain. The intervention consisted of an Advanced Life Support (ALS) training program implemented in a blended learning format that combined online theoretical instruction with in-person practical sessions. The course integrated theoretical modules, hands-on workshops, and simulation-based exercises aligned with international resuscitation guidelines. The Brief Inventory of Emotional Intelligence and the Rosenberg Self-Esteem Scale were used. Data analysis was performed using nonparametric tests and the Wilcoxon test to assess pre- and post-intervention variations.ResultsCorrelations between self-esteem and several dimensions of emotional intelligence showed significant post-intervention increases. The intrapersonal and interpersonal factors of emotional intelligence showed significant improvements in their mean scores. However, no significant changes in stress management, mood, or self-esteem were observed in the total sample.ConclusionThe study highlights the efficacy of incorporating emotional intelligence and self-esteem training in the training of health professionals, demonstrating improvements in stress management and adaptability. The variations in the effects of the intervention suggest the need to adapt future interventions to the specific characteristics of each profession. Integrating these programs into health education could significantly enhance the quality of patient care and the wellbeing of health professionals.